Effect of debate strategy on EFL learners, speaking proficiency at Ibb University and their attitudes towards it. - Ghalib, Mukhtar; Almuslimi, Fazee (International Journal of Language and Literary Studies, 2023)
This study was conducted to investigate the effect of debate strategy on developing learners’ speaking proficiency at Ibb University and their attitudes towards it. Due to the nature of the study, the researcher used a quasi-experimental research. Through a mixture of qualitative and quantitative methods used in the study, an oral speaking test, a checklist observation and questionnaire were conducted on 32 learners at level one, English Department, Ibb University in the second semester of the year 2022. To analyze the data, the researcher used means, standard deviations and a t test. The participants went through ten debate sessions lasted for two months and fifteen days and sat for a test before and after using the debate strategy. Using checklist observation, the participants’ performance in the tests were evaluated. To reveal their attitudes towards the effect of debate strategy on their speaking proficiency, the participants were asked to respond to the questionnaires that were analyzed later. The findings revealed that participants’ level of speaking proficiency greatly developed and that there was a significant difference in the participants’ scores before and after using the debate strategy, which suggested that the effect of debate strategy on the learners’ speaking proficiency was very high. The participants’ attitudes they held towards the debate strategy were highly positive. That means the debate strategy, was very successful in developing learners’ speaking proficiency at Ibb University, and, therefore, it was recommended for teachers, specialists, etc. to teach English, mainly the speaking skill, through debate strategy.